Masculinity and men's health service use across four social generations: Findings from Australia's Ten to Men study - Jacquie McGraw; Katherine M. White; Rebekah Russell-Bennett (Elsevier, 2021)
There is a perception that traditional masculine ideals, usually thought deleterious for men's health outcomes, are no longer as relevant for younger social generations such as Millennials as they are for older social generations such as Baby Boomers. Yet, in Australia, there remains a disparity between younger men's and women's health outcomes and use of health services. Conformity to traditional masculinity is often cited as a barrier to men's positive health behaviours but conceptualisation of the construct is contested. We analysed a selected secondary dataset (n = 14,917) of Australian males aged between 15 and 55 years from Ten to Men: The Australian Longitudinal Study on Male Health. We examined the role of conformity to traditional masculine norms in predicting likelihood of regular primary and preventative health services use for different social generations. Analyses included mediated regression and adjusted logistic regression. Conformity to ten of the eleven specific traditional masculine norms predicted likelihood of increased or decreased regular health service use depending on the generation and health service type. Specific traditional masculine norms play a complex role in men's use of distinct health service types for different generations of Australian males. Practitioners wishing to increase men's engagement with health services should consider gender-sensitive approaches that leverage specific masculine norms relevant to the age cohort to drive positive outcomes in men's health.